POLITYCZNE ZNACZENIE RUCHU ŚLĄZAKOWSKIEGO W OBLICZU PLEBISCYTU NA ŚLĄSKU CIESZYŃSKIM - Wnętrzak, Grzegorz (In Gremium. Studies in History, Culture and Politics, 2012)
THE POLITICAL IMPORTANCE OF THE SZLONZAKIAN MOVEMENT IN THE CIESZYN SILESIA PLEBISCITE This article deals with the political importance of the Szlonzakian movement in Cieszyn Silesia in a crucial time for this area, after the fall of the Austro-Hungarian monarchy and announcement of a plebiscite which aimed at establishing its dependency from Poland or Czechoslovakia. The announcement of the plebiscite in September 1919 was perceived in Poland as the first step to a definite win in the battle for Silesia. The author tends towards the view that it was the declared supporters of Józef Każdoń who determined the result of the voting. The fact that the leaders of the Silesian People’s Party were clearly in favour of the Czechoslovakian side indicates that Poland would have suffered a defeat in the plebiscite. The article analyses many sources which have not yet been used to point out the rivalry between the Polish people and Szlonzakians who supported the Czechs, especially in the Eastern part of Cieszyn Silesia which was dependent from Poland after 1920. Reports of Polish activists in which they express their uncertainty about the developments in the region are particularly interesting. The article also analyses attempts, mostly failed, at winning Szlonzakians and Germans over what indicates their significance in the plebiscite.